PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 42 PEKANBARU - Wijayanti '; Syahrilfuddin '; Guslinda ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated because of the problems of the poor results of students learning mathematics, as seen from the average value of 69.4 students. Of the 42 students who reached the KKM is 20 students (47.6%), while students who do not reach the KKM is 22 students (52.38%). KKM predetermined value is 72. Based on these problems need action research based by applying the model of cooperative Team Assisted Individualization (TAI). This study aims to improve student learning outcomes SDN 42 Pekanbaru grade math VA academic year 2015/2016 the number of students as many as 42 people consisting of 15 male students and 27 female students. This research was conducted in two cycles. The first cycle consisted of three meetings, the two face to face meetings and one meeting daily test cycles I. II consists of three sessions, the two face to face meetings and one meeting daily tests II. With the implementation of cooperative learning model Team Assisted Individualization (TAI) can increase student mathematics learning outcomes, can be seen from the percentage of teachers in the first cycle of activity increase of 60.4% in the second cycle becomes 72.9%. The percentage of student activity in the first cycle with a 62.47% increase in cycle II became 77.08%. While the percentage of mathematical completeness results in a base score of 47.6% with an average of learning - 69.4 average increase in the first cycle to 80.9% with an average of 84.8 and the percentage increase learning outcomes by 22.19% and cycle II completeness percentage increased to 83.3% with an average of 85.8 and the improvement of learning outcomes increased by 23.7%. From the description it can be seen that through the implementation of cooperative learning model Team Assisted Individualization (TAI), can improve student learning outcomes SDN 42 Pekanbaru math class.Keywords : Cooperative Learning Model Team Assisted Individualization (TAI) type , Mathematics learning outcomes2PENERAPAN MODEL PEMBELAJARAN KOOPERATIF